Not an ordinary bank but a great engine of state: The Bank of England and the British economy, 1694-1844 - Patrick Karl O'Brien; Nuno Palma (The European Association for Banking and Financial History (EABH), 2020)
From its foundation as a private corporation in 1694 the Bank of England extended large amounts of credit to support the British private economy and to support an increasingly centralized British state. The Bank helped the British state reach a position of geopolitical and economic hegemony in the international economic order. In this paper, we deploy recalibrated financial data to analyse an evolving trajectory of connections between the British economy, the state, and the Bank of England. We show how these connections contributed to form an effective and efficient fiscal-naval state and promoted the development of a system of financial intermediation for the economy. This symbiotic relationship became stronger after 1793. The evidence that we consider here shows that although the Bank was nominally a private institution and profits were paid to its shareholders, it was playing a public role well before Bagehot's doctrine.
Keywords: H41; N13; N23; N43; 330; Bank of England; State-building institutions; National defence